2016
DOI: 10.1093/nar/gkw461
|View full text |Cite
|
Sign up to set email alerts
|

Defining the essential function of FBP/KSRP proteins:DrosophilaPsi interacts with the mediator complex to modulateMYCtranscription and tissue growth

Abstract: Despite two decades of research, the major function of FBP-family KH domain proteins during animal development remains controversial. The literature is divided between RNA processing and transcriptional functions for these single stranded nucleic acid binding proteins. Using Drosophila, where the three mammalian FBP proteins (FBP1-3) are represented by one ortholog, Psi, we demonstrate the primary developmental role is control of cell and tissue growth. Co-IP-mass spectrometry positioned Psi in an interactome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…In wild‐type, Pros nuclear entry triggers pupal NB differentiation (Maurange et al , ), which is regulated by the mediator complex in response to the pupal ecdysone pulse (Homem et al , ). Interestingly, the mediator complex also regulates myc expression (Guo et al , ). It is thus tempting to speculate that a developmentally regulated reduction of myc expression triggers pupal NB differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In wild‐type, Pros nuclear entry triggers pupal NB differentiation (Maurange et al , ), which is regulated by the mediator complex in response to the pupal ecdysone pulse (Homem et al , ). Interestingly, the mediator complex also regulates myc expression (Guo et al , ). It is thus tempting to speculate that a developmentally regulated reduction of myc expression triggers pupal NB differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila ortholog of FUBP1, called Psi, is required for transcriptional initiation and elongation of RNA Pol II across the MYC gene. Additionally, Psi interacts with the Mediator transcriptional complex, likely playing a role to integrate multiple signaling inputs on the MYC promoter . The ortholog of FIR, encoded by the Half pint ( Hfp ) gene in Drosophila , is required for repression of Drosophila MYC .…”
Section: Single‐stranded Nucleic Acid Binding Proteins Regulate Confomentioning
confidence: 99%
“…Recent Drosophila genetic studies revealed a major developmental function of the sole FUBP ortholog (Psi); interaction with the RNA Polymerase II (Pol II) Mediator complex, regulation of MYC expression and control of cell and tissue growth. 5 …”
Section: Prefacementioning
confidence: 99%
“…43 Further to these RNA processing functions, and in accordance with Psi behaving in a functionally analogous manner to FUBP1, recent studies revealed a key role for Psi in sustaining developmentally regulated MYC transcription and, thus, cell and tissue growth. 5 Moreover, like FUBP1, 44 Psi has potent transcriptional activator capacity in vitro, mediated by conserved tyrosine-rich domains (YM1 and YM2 repeats). 5 The Psi interactome is predominantly comprised of Pol II transcriptional machinery (63% of the top 65 Psi-interactors).…”
Section: Drosophila Fubp1/psi Interacts With Mediator To Control Tissmentioning
confidence: 99%
See 1 more Smart Citation